SISTEM INFORMASI AKADEMIK FAKULTAS PERIKANAN UNIVERSITAS KRISTEN PALANGKA RAYA BERBASIS WEB - Enny Dwi Oktaviyani; Vincentius Abdi Gunawan; Utami Puji Kristianingsih (Universitas Palangka Raya, 2015)
Academic information system (SIAKA) is an information which is built to support academic process system that include schedule of lecturer, students’ reregistration, students’ data, academic calender, filling KRS, and see students’ KHS and then can print out the KHS by online. Fishing Faculty not have yet academic information system that handle with online in based Web. In conducting is still done by manual. On Academic Information System Fishing Faculty Kristen University of Palangka Raya in basic Web, to help in handling filled KRS, Printed and see the Students’ KHS, and can see schedule of lecturer and academic calender by online, so students do not again fill the KRS by manual system and take easy to give information about schedule of lecturer, examination schedule, and academic calender by online so not need again paste the information on the board of anouncement, so with this system can help to easy all activities that any in Fishing Faculty Cristian University of Palangka Raya.In developing aplication, this website use language program of PHP, database MySQL and Method Syclus developing Clasic Aplication which is called waterfall with Five step. The steps involped Analysis, Design, Coding, Testing, and Maintenance. On step examin program using blackboxThe application process consists of the process of inputting data, processing the data, print the data, then stored the data in database. It would be help to give more information about christian university of palangka raya and the academic system at the fishing faculty for the visitors, the students and lecturer online